2015
DOI: 10.1007/s11356-015-4869-9
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity levels and heavy metals in the urban soil of Central Serbia

Abstract: Radioactivity concentrations and heavy metal content were measured in soil samples collected from the area of Kragujevac, one of the largest cities in Serbia. The specific activities of (226)Ra, (232)Th, (40)K and (137)Cs in 30 samples were measured by gamma spectrometry using an HPGe semiconductor detector. The average values ± standard deviations were 33.5 ± 8.2, 50.3 ± 10.6, 425.8 ± 75.7 and 40.2 ± 26.3 Bq kg(-1), respectively. The activity concentrations of (226)Ra, (232)Th and (137)Cs have shown normal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…The methods used to assess the effective dose and excess cancer risk were from previous studies. [34][35][36][37][38][39] The effective dose and the excess risk of lung cancer were derived from survey results and annual radon concentration measurements. Effective dose was calculated using criteria described in the UNSCEAR report.…”
Section: Analysis Methods Of Risk Levelsmentioning
confidence: 99%
“…The methods used to assess the effective dose and excess cancer risk were from previous studies. [34][35][36][37][38][39] The effective dose and the excess risk of lung cancer were derived from survey results and annual radon concentration measurements. Effective dose was calculated using criteria described in the UNSCEAR report.…”
Section: Analysis Methods Of Risk Levelsmentioning
confidence: 99%
“…The specific activity of 232 Th was determined by the gamma-ray lines of 228 Ac (at the energies of 338.3, 911.1 and 968.9 keV) and 208 Tl (at the energies of 583.0 and 860.6 keV). The gamma ray lines at 1460.7 and 661.6 keV were used for estimating specific activities of 40 K and 137 Cs, respectively (MILENKOVIC et al, 2015). For activity and background, a timer of 252,000 seconds was set.…”
Section: Radiactivity Measurmentmentioning
confidence: 99%
“…Investigation of radionuclide content in the soil has also been conducted in urban areas (Grdović et al, 2010;Janković Mandić and Dragović, 2010;Dragović et al, 2012;Milenković et al, 2015;Mitrović et al, 2016b;Vukašinović et al, 2018), agriculture soil (Vukašinović et al, 2009(Vukašinović et al, , 2010Bikit et al, 2011;Mitrović et al, 2013b;Forkapić et al, 2017) and in the vicinity of industrial plants (Vitorović et al, 2012;Vukašinović et al, 2014). Gammaspectrometric determination of 238 U in the soil sampled from 21 different locations in Serbia and Montenegro showed that uranium content ranged from 1.28 ppm on Slatina (approximately 15.7 Bq/kg) to 4.80 ppm in Vranje (approximately 58.8 Bq/kg), with the mean value of 2.76 ppm (approximately 33.8 Bq/kg) (Dragović et al, 2006b).…”
Section: Radionuclides In the Soil Of Serbiamentioning
confidence: 99%